Achieving Success: Transformative Branding and Digital Marketing Strategies to Elevate Wotanmas Jedong MSMEs: Meraih Kesuksesan: Strategi Transformatif Branding dan Pemasaran Digital untuk Mengangkat UMKM Wotanmas Jedong - Waluyo, Sabka Ardi; Pratama, Handraswara; Rachamawati, Aisyah; Prasetya, Atina Nabila Ade; Yani, Muhammad (Proceedings of The ICECRS, 2023)
The goals of this service include efficient digital marketing. This is to increase the visibility and attractiveness of Wotanmas Jedong MSMEs in society by using effective digital marketing strategies. Apart from that, the aim of this service is also to equip Wotanmas Jedong MSME players with digital marketing skills that will help them develop and develop. This service method involves Wotanmas Jedong MSME owners taking digital marketing training, which includes teaching them about things like SEO, social media, and e-commerce, as well as designing and implementing digital marketing strategies that include innovative content, social media campaigns, and promotions. online to increase visibility and customer interest. This dedication has resulted in increased awareness of the Wotanmas Jedong UMKM brand among the target market, as demonstrated by increased interactions and followers on social media. Apart from that, optimizing digital marketing, which means implementing effective digital marketing strategies, increasing competitiveness and market penetration through online platforms. This service can increase the income and sustainability of MSMEs, which can improve local economic prosperity and encourage local economic growth. Highlights: Boosting Wotanmas Jedong MSMEs through comprehensive digital marketing education. Implementing strategic SEO, social media, and e-commerce techniques for enhanced online presence. Driving local economic growth by increasing competitiveness and market penetration through optimized digital marketing. Keywords: Brand Awarenes, Digital Marketing, UMKM